Quantitative histopathologic profiling of arterial dissection-related thrombi in acute ischemic stroke: etiological comparisons - Cai, Gang; Fang, XuMing; Li, Jun; Cheng, YuanHua; Zhang, YanHui; Chu, Lan (Frontiers in Neurology, 2025)
IntroductionArterial dissection is an important etiology of stroke in young adults and may demonstrate distinct thrombus characteristics. While most studies have focused on compositional differences between cardioembolic (CE) and non-cardioembolic thrombi, systematic analyses of dissection-related thrombi remain scarce. This study characterized the compositions of dissection thrombi, compared them with those of non-dissection thrombi, and explored compositional variations among stroke etiologies.Materials and methodsWe retrospectively analyzed the clinical data and thrombi of 230 patients with acute ischemic stroke (AIS). The thrombi were stained with hematoxylin and eosin (H&E) and digitally scanned, and their composition was analyzed based on quantified red blood cell (RBC), fibrin/other component (F/O), and white blood cell (WBC) ratios and the total thrombus area. Comparisons were made between dissection-related AIS and non-dissection etiologies (large artery atherosclerosis [LAA], CE, stroke of other determined etiology [SOE], and stroke of undetermined etiology [SUE]).ResultsAmong the 230 patients with acute ischemic stroke, 16 (7.0%) had dissection-related stroke and 214 (93.0%) had non-dissection stroke (59 LAA, 124 CE, 2 SOE, and 29 SUE). Compared to those in the non-dissection group, the patients in the dissection group were significantly younger and had a lower prevalence of hypertension and atrial fibrillation but higher tandem lesion frequency (all p < 0.05). Regarding the thrombus characteristics, no significant differences were observed in the RBC, F/O, or WBC ratios between the dissection and non-dissection groups or subgroups. However, the LAA thrombi were significantly smaller than those in the dissection, CE, and SUE groups (p < 0.05).ConclusionThe H&E-based thrombus composition analysis did not differentiate arterial dissection from other stroke etiologies. LAA thrombi exhibited the smallest thrombus burden among the major stroke subtypes.